2020
DOI: 10.1177/0300060520926010
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and fraction of exhaled nitric oxide in obstructive sleep apnea in adults

Abstract: Objective This study aimed to evaluate the relationship between obstructive sleep apnea (OSA) and the fraction of exhaled nitric oxide (FENO), and to assess the effect of risk factors of airway inflammation on OSA. Methods Medical records of patients in the Respiratory Sleep Center at Chao-Yang Hospital in Beijing between January 2015 and June 2017 were analyzed. All patients were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, upper airway tissue biopsies from patients with OSA showed subepithelial oedema and increased inflammatory cell infiltration [ 28 , 37 , 38 , 39 ]. In addition, some studies have also reported increased levels of exhaled nitric oxide in patients with OSA [ 40 , 41 , 42 , 43 ]. However, a recent meta-analysis showed no significant differences in exhaled nitric oxide relative to control groups [ 44 ].…”
Section: Osa and Inflammationmentioning
confidence: 99%
“…Indeed, upper airway tissue biopsies from patients with OSA showed subepithelial oedema and increased inflammatory cell infiltration [ 28 , 37 , 38 , 39 ]. In addition, some studies have also reported increased levels of exhaled nitric oxide in patients with OSA [ 40 , 41 , 42 , 43 ]. However, a recent meta-analysis showed no significant differences in exhaled nitric oxide relative to control groups [ 44 ].…”
Section: Osa and Inflammationmentioning
confidence: 99%